Peneguhan Ketahanan Negara Melalui Penguatan Ketahanan Keluarga dan Pendidikan Pranikah: Telaah Modal Sosial Pesantren - Qomaro, Galuh Widitya (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Pesantren as the oldest Islamic educational institution in Indonesia is so far still exists as a social education institution (al-haiah al-ta'lîm wa al-tarbiyyah), guidance services for the community (al-haiah al ta'âwuny wa al-takâfuly wa al-ittijâhi), and struggle (al-haiah al-jihadi li'izzi al-Islami wa al-muslimîn). Pesantren's social role in community life continues to survive and can significantly change social reality. The education system and social values built by the Pesantren, sociologically, can be social capital to influence social actions and behavior, including to prevent the disharmony from fundamental aspects, one of which is by building family resilience. This article is a preliminary study to measure the role of Pesantren’s value and its contribution as one of the national development stakeholders in promoting premarital education for students and in family studies for communities outside the Pesantren